2006
DOI: 10.1111/j.1442-2042.2006.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute urinary retention as a result of a bladder diverticulum

Abstract: An 11-month-old infant presented with acute urinary retention. He had presented 3 months earlier with complaints of an enlarging abdominal mass that was initially diagnosed as a mesenteric cyst on ultrasonography. Voiding cystourethrogram revealed a large bladder diverticulum. Bladder diverticulum should be a differential diagnosis in children, especially male, presenting with urinary retention, fever and an abdominal mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Studies which included patients above 18 years of age, reported UR due to other etiologies, or their full text was not accessible, were excluded. With regards to bladder diverticula causing UR, 20 articles, including 49 cases, were found, while only four articles, including five cases, were found for MDC 8–31 . Besides, no report for UR due to ureteral stump syndrome was found with the mentioned keywords.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which included patients above 18 years of age, reported UR due to other etiologies, or their full text was not accessible, were excluded. With regards to bladder diverticula causing UR, 20 articles, including 49 cases, were found, while only four articles, including five cases, were found for MDC 8–31 . Besides, no report for UR due to ureteral stump syndrome was found with the mentioned keywords.…”
Section: Discussionmentioning
confidence: 99%
“…This deranged anatomy results in VUR. 11 Congenital bladder diverticula most often present with urinary tract infection, but hematuria, abdominal pain, or an abdominal mass may also be present. Inguinal hernias containing bladder diverticula have also been reported.…”
Section: Discussionmentioning
confidence: 99%